Analisis Mata Pencaharian Penduduk Reteh Menanam Pinang untuk Menambah Income - Anisa Anisa; Naskah Naskah; Daniatul Maghfiroh; Hafiz Taufiqurrahman Hashibuan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The largest livelihood of the Republic of Indonesia is the agricultural and plantation sectors. One of the plantation crops is the Areca nut plant. Indragiri Hilir Regency is one of the regencies that cultivates areca nuts. Indragiri Hilir Regency or better known as the land of a thousand bridges has 20 sub-districts, 39 villages, and 197 villages. Reteh is one of the sub-districts in Indragiri Hilir, where almost all the residents of this sub-district have areca nut land. This research method uses a literature study method. The results of this study show that areca nut plants can increase the income of the residents of Reteh District. So that they can meet daily needs. However, from the end of 2023 until now, the price of areca nuts has plummeted, making areca nut farmers struggling to meet their needs. "To what extent, is the government's assistance solution?" With conditions like this, farmers really hope for a solution from the government to improve the economy amidst the current plummeting price of areca nuts, so that the price of areca nuts can improve like in previous years so that the economy of farmers, especially areca nut farmers in Reteh District, can prosper again.